Theoretical and experimental studies on a Q-switching operation in an erbium-doped fiber laser using vanadium oxide as saturable absorber - Nady, Ahmed; Latiff, Anas Abdul; Numan, Arshid; Raymond Ooi, Chong Heng; Harun, Sulaiman Wadi (IOP Publishing, 2018)
We introduce theoretical analysis for a passively Q-switching operation in an erbium-doped fiber laser (EDFL) with a saturable absorber (SA). Peak power, repetition rate, and pulse duration have been calculated as functions of pump power and cavity length. The simulation results are compared with the passively Q-switched EDFL demonstrated using vanadium oxide (V2O5) as SA. The nonlinear saturable absorption of the V2O5-SA is characterized by a modulation depth of 7% with a saturation intensity of 71 MW cm-2. This is the first demonstration of a fiber laser based on a V2O5-SA that introduces new opportunity for photonic applications. The introduced theoretical model could be highly useful for understanding and improving Q-switched EDFLs based on a SA.